2022
DOI: 10.1186/s12974-022-02455-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of lipocalin-2 in surgery-induced cognitive decline in mice: a signal from neuron to microglia

Abstract: Background Perioperative neurocognitive disorders (PNDs) are common complications observed among surgical patients. Accumulating evidence suggests that neuroinflammation is one of the major contributors to the development of PNDs, but the underlying mechanisms remain unclear. Methods qPCR and ELISA analysis were used for detecting LCN2 and cytokine levels. cx3cr1CreER/−:: R26iDTR/− crossed mouse line was used for microglia depletion; intracranial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Inhibition of NF‐κB can reduce the expression of pro‐inflammatory cytokines (such as IL‐6, IL‐1β, and TNF‐α) and increase the expression of BDNF, thereby ameliorating the cognitive decline of diabetic mice 51 . The involvement of Lcn2 in apoptosis extends to insulin resistance, cancer, and nervous system diseases 52,53 . However, further investigation is required to determine its potential role in particle‐induced conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of NF‐κB can reduce the expression of pro‐inflammatory cytokines (such as IL‐6, IL‐1β, and TNF‐α) and increase the expression of BDNF, thereby ameliorating the cognitive decline of diabetic mice 51 . The involvement of Lcn2 in apoptosis extends to insulin resistance, cancer, and nervous system diseases 52,53 . However, further investigation is required to determine its potential role in particle‐induced conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 51 The involvement of Lcn2 in apoptosis extends to insulin resistance, cancer, and nervous system diseases. 52 , 53 However, further investigation is required to determine its potential role in particle‐induced conditions. Our findings that CS exposure augmented astrocytic Lcn2 and neurotoxicity in the hippocampus are in agreement with the bulk of the research.…”
Section: Discussionmentioning
confidence: 99%
“…Excess in ammatory factor production in the aged brain following peripheral trauma is dependent on the activation of microglia [44][45][46]. Microglia, which are important immune cells in the CNS, are regarded as tissue macrophages in the brain [47].…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative neurocognitive disorders (PND), including POD and postoperative cognitive dysfunction (POCD), are common following anesthesia and surgery in older patients and signi cantly increase morbidity and mortality [16,17]. Neuroin ammation in the hippocampus, including microglial in ammatory response and neuronal apoptosis, plays an essential role in cognitive dysfunction [18,19]. Initial evidence has shown that rats transfused with old RBCs or receiving free-Hb and mice receiving intracerebral heme injection suffer from neuroin ammation and neurological de cits [9,20].…”
Section: Introductionmentioning
confidence: 99%